Nyai Brintik's Tomb As A Religious Tourism Site To Increase Tourist Visits In Kampung Pelangi - Edgar David Richardo Daeli; Nina Mistriani (Brilliant International Journal Of Management And Tourism, 2024)
The WO (Weaknesses-Opportunities) strategy focuses on overcoming weaknesses such as limited supporting facilities and lack of promotion by taking advantage of external opportunities such as high interest in religious tourism and promotion through print and digital media. This involves increasing promotion and marketing and developing attractive religious tourism programs. The WT (Weaknesses-Threats) strategy focuses on overcoming internal weaknesses, such as limited supporting facilities and competition from other tourist destinations, by facing external threats, such as cultural values ​​and economic uncertainty changes. This involves investment in developing tourism infrastructure and improving the quality of services at Nyai Brintik Tomb. By implementing these strategies, it is hoped that the potential for religious tourism at the Nyai Brintik Tomb can be optimized effectively, increasing the number of tourist visits, increasing tourism income, and strengthening local cultural identity. Apart from that, the development of religious tourism at the Nyai Brintik Tomb can also contribute to the sustainable development of the Mount Brintik area as a whole by paying attention to aspects of environmental preservation, local economic development and community empowerment. Thus, the Nyai Brintik Tomb has the potential to become one of the leading religious tourism destinations in the city of Semarang, attracting visitors from various groups and providing a memorable and meaningful tourist experience.